IMPACT OF THE SELECTIVITY AND HALF-LIFE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS ON THE DEVELOPMENT OF SUBCLINICAL KIDNEY INJURY - S. A. Zhigalov; V. V. Marasaev (Современная ревматология)
Objective: to investigate the impact of the selectivity and half-life of nonsteroidal anti-inflammatory drugs (NSAIDs) on the development of subclinical kidney injury (SKI). A standard physical examination was made.Patients and methods. The study included 80 patients with a verified rheumatoid arthritis (RA) diagnosis. The patients filled in a specially designed questionnaire to explore a history of drug use. As markers of SKI, the investigators determined the concentrations of albumin, α1-microglobulin (α1-MG), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) in urine. A control group consisted of 20 apparently healthy individuals matched for age and gender.Results. 80 patients suffering from RA received drug therapy. Of them, 82.5% and 87.5% took NSAIDs and disease-modifying antirheumatic drugs, respectively. The levels of SKI markers were compared in three groups of the examinees: 1) NSAID-treated patients; 2) NSAID-untreated patients; 3) a control group. There were statistically significant differences between all the groups (p<0.05). Comparison of the levels of SKI markers revealed no statistically significant difference in the groups receiving selective cyclooxygenase-2 (COX-2) inhibitors (n=18.6%), in those taking nonselective ones (n=68.6%), and the control group. Comparison of the levels of SKI markers demonstrated significantly higher >< 0.05). Comparison of the levels of SKI markers revealed no statistically significant difference in the groups receiving selective cyclooxygenase-2 (COX-2) inhibitors (n=18.6%), in those taking nonselective ones (n=68.6%), and the control group. Comparison of the levels of SKI markers demonstrated significantly higher α1-MG levels in the long-acting NSAID groups (n=8.6%) than in the short-acting NSAID group (n=80%). ALT, ALP, and microalbuminuria showed a similar trend that failed to reach statistical significance.Conclusion: NSAIDs remain a group of medications with a certain nephrotoxic effect. At the same time, the design of selective COX-2 inhibitors has failed to solve the problem of nephrotoxicity. NSAIDs with long half-lives are characterized by greater nephrotoxicity. The available data provide preconditions for the more differentiated use of NSAIDs, particularly in patients with RA.